2014
DOI: 10.1380/ejssnt.2014.400
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric-Pressure Plasma Jet Irradiation onto Main Components of the Cell Wall and Membrane of <i>Escherichia Coli </i>

Abstract: To clarify the mechanism underlying the inactivation of Escherichia coli (E. coli) cells subjected to atmosphericpressure argon (Ar) plasma jet irradiation, we focused on phospholipids, the main components of the cell wall and membrane of E. coli. Commercially available standard samples of phospholipids, phosphatidylethanolamine (PE) and phosphatidylglycerol (PG) were irradiated with an atmospheric-pressure Ar plasma jet in air for 5 s. The phospholipids irradiated with the plasma jet were separated by thin-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…24) Generally, the oxidation of phospholipids under physiological condition proceeds on its hydrocarbon chain with double bonds; but recently, Kuwahata et al reported a strong head-group dependence in the plasmainduced reaction of phospholipids. 65) The atmosphericpressure plasma irradiation of a dried film of a lipid extracted from Escherichia coli selectively breaks the ester bond of phosphatidylglycerol, producing lysophosphatidylglycerol, while phosphatidylethanolamine remains nearly unchanged. Further studies are needed to identify the species critical to the decrease in diffusion coefficient among the numerous candidates for plasma-induced ROS to clarify their mechanism of reaction with lipid molecules, and to determine the chemical structures of oxidatively modified phospholipids.…”
Section: Resultsmentioning
confidence: 99%
“…24) Generally, the oxidation of phospholipids under physiological condition proceeds on its hydrocarbon chain with double bonds; but recently, Kuwahata et al reported a strong head-group dependence in the plasmainduced reaction of phospholipids. 65) The atmosphericpressure plasma irradiation of a dried film of a lipid extracted from Escherichia coli selectively breaks the ester bond of phosphatidylglycerol, producing lysophosphatidylglycerol, while phosphatidylethanolamine remains nearly unchanged. Further studies are needed to identify the species critical to the decrease in diffusion coefficient among the numerous candidates for plasma-induced ROS to clarify their mechanism of reaction with lipid molecules, and to determine the chemical structures of oxidatively modified phospholipids.…”
Section: Resultsmentioning
confidence: 99%
“…Semipurified samples dissolved in LC–MS-grade methanol were analyzed on LCMS-IT-TOF quadrupole ion trap time-of-flight mass spectrometer (Shimadzu, Japan) according to Kuwahata et al . [ 18 ].…”
Section: Methodsmentioning
confidence: 99%